Heat transfer characteristic research during jet impinging on top/bottom hot steel plate. (October 2016) - Wang, Bingxing; Guo, Xitao; Xie, Qian; Wang, Zhaodong; Wang, Guodong
Highlights: The heat transfer of a jet impinging on top or bottom surface was investigated. The differences of the heat flux and the wetting front propagation were studied. The heat transfer ability increases with the waterflow and reduces with the distance. The wetting front propagation is governed by the ability water flow transporting the bubbles. Abstract: Recently, the impinging jet has been widely used in the controlled cooling process following hot rolling as a key technology to develop an ultra-fast cooling system. The hot plate/strip undergoes a symmetrically cooling process on the top and bottom surface. Under this consideration, a laboratory apparatus was established to investigate the heat transfer characteristics of a single circular jet impinging on the top or bottom surface of the plate. The results demonstrate that the differences in the heat transfer performance and the wetting front propagation phenomena are noticeable. The top-surface heat flux is slightly higher than the bottom one in the measured cooling region. The heat flux increases with the water flow rate, and decreases with the nozzle-to-surface distance. However, with the increase of radial distance, the top-surface wetting front expanding speed is significantly lower than that of the bottom-surface, especially when the water flow rate is higher than 2 l/min. The results indicate that jet velocity is the critical factor to generate higher cooling performance during both impinging processes. The present study is useful for designing an ultra-fast cooling device and the optimized cooling parameters will enhance the cooling efficiency and cooling uniformity of the industrial ultra-fast cooling equipment.